2022
DOI: 10.1093/ofid/ofac373
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus in Uganda: Clinical Outcomes of Adult Patients Hospitalized at a Tertiary Health Facility Between 2011 and 2020

Abstract: Background Tetanus is a vaccine-preventable infectious disease associated with high mortality rates. Increased vaccination coverage globally and locally has resulted in substantial declines in the number of individuals diagnosed with tetanus. We report annual trends in tetanus admissions and deaths over a decade at a national referral hospital in Uganda. Methods This was a retrospective cohort study, using data from an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The overall median duration of hospitalization of patients with tetanus in this study was 29.5 days, which was similar to a recent report of low mortality (2.8%) from Vietnam (30). The median hospital stay of the latter was 25 days, which was much longer than the hospitals reported in some areas with high mortality (10,18). Severe tetanus, in particular, requires longer ICU time, more mechanical ventilation requirements and longer hospital stay, remains a significant burden on healthcare services.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The overall median duration of hospitalization of patients with tetanus in this study was 29.5 days, which was similar to a recent report of low mortality (2.8%) from Vietnam (30). The median hospital stay of the latter was 25 days, which was much longer than the hospitals reported in some areas with high mortality (10,18). Severe tetanus, in particular, requires longer ICU time, more mechanical ventilation requirements and longer hospital stay, remains a significant burden on healthcare services.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is no uniform guideline for wound debridement in patients with tetanus. Some published studies on the prognosis of tetanus have not reported the rate of implementation of debridement ( 10 , 29 , 30 ). We believe that debridement is essential to control the symptoms of tetanus and improve the prognosis, especially for severe tetanus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation